Characterization on the reduction of burst release via biodegradable polymers from chlorhexidine-release on coated Foley urinary catheter by chlorhexidine-loaded micelles - Siriwan Srisang (2020)
© 2020 Published under licence by IOP Publishing Ltd. In this work, chlorhexidine-loaded block copolymer was fabricated into micelles (CHX-micelles) and was then coated on foley urinary catheter by dip technique. The number cycles of coating were alternated the bilayers between (CHX-micelles) and poly(acrylic acid) which presented the suitable cycles of coating at 90 bilayers. This cycle of coating presented enough CHX quantity on coated catheter but their still showed burst CHX-release in early stage at first day. Hence, poly (lactic acid), PLA and poly (-caprolactone), PCL were also used to coat on top of 90 bilayers of catheter surface to reduce the burst release. The CHX quantity was then investigated on coated catheter and were studied the CHX-release. Results showed that the coated catheters at 90 bilayers and then coated the PLA and PCL presented the reduction of burst CHX-release from 80% to 42% for PLA coating and 38% for PCL. Moreover, coating PCL nanospheres (PCL-NS) on coated of 90 bilayers (CHX-micelles/PAA) can assist to reduce the burst release of CHX and prolonged the CHX-release up to two weeks. Thus, this strategy can be reduced the burst CHX-release on coated urinary catheter at early stage and can be prolonged the CHX-release.